A design-based approach for developing a teaching aid for dyslexic children/ Norarifah Ali ... [et al.] - Ali, Norarifah; Md Hashim, Azhari; Abdullah, Mohamad Hariri; Alias, Roslinda; Yaakob, Muhammad Nidzam (Universiti Teknologi MARA, Perak, 2023)
This article presents a design-based approach for developing a specialized teaching aid for dyslexic children, with a focus on enhancing their reading skills and engagement. Dyslexia, a common learning disorder that affects reading abilities, requires tailored interventions to effectively support dyslexic learners. By integrating design thinking principles and the Orton-Gillingham approach, this study outlines a comprehensive design process for creating an innovative teaching aid. The approach emphasizes user-centeredness, iterative prototyping, and multisensory experiences as key elements to address the diverse learning needs of dyslexic children. The study employed a qualitative research method, conducting interviews with dyslexia teachers and observing dyslexic children in a classroom setting to gather data. Thematic analysis was used to analyze the interview data. The development of this teaching aid holds promise for improving reading proficiency and fostering greater engagement in learning among dyslexic children. The findings of this study contribute to the field of education by offering insights into the design and development of effective teaching aids for dyslexic children.